2016
DOI: 10.1007/s00572-016-0711-6
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial native bacteria improve survival and mycorrhization of desert truffle mycorrhizal plants in nursery conditions

Abstract: Sixty-four native bacterial colonies were isolated from mycorrhizal roots of Helianthemum almeriense colonized by Terfezia claveryi, mycorrhizosphere soil, and peridium of T. claveryi to evaluate their effect on mycorrhizal plant production. Based on the phylogenetic analysis of the 16S rDNA partial sequence, 45 different strains from 17 genera were gathered. The largest genera were Pseudomonas (40.8 % of the isolated strains), Bacillus (12.2 % of isolated strains), and Varivorax (8.2 % of isolated strains). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…to minimize large interannual fluctuations. For the proper management of T. claveryi plantations, it is essential to identify the biotic and abiotic factors that could explain this variability (Navarro-Ródenas et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…to minimize large interannual fluctuations. For the proper management of T. claveryi plantations, it is essential to identify the biotic and abiotic factors that could explain this variability (Navarro-Ródenas et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have concentrated on mycorrhization helper bacteria (MHB) in facilitating mycorrhizal colonization of roots in forest nursery environments(43, 71). Rich in bacteria in the mycorrhizal roots, mycorrhizosphere soil and peridium of desert truffles may be used to increase the survival and mycorrhization in the desert truffle plant production system at a semi-industrial scale(72). The associated bacteria of Truffle brûlés are Pseudomonas and Flavobacteriaceae (73).…”
Section: Discussionmentioning
confidence: 99%
“…strain that promoted ectomycorrhizal colonization of Pisolithus tinctorius and Lactarius insulsus on Populus deltoids trees. Another example is that of Navarro-Ródenas et al (2016) who isolated a Pseudomonas mandelii strain that increased mycorrhizal colonization of Terfezia claveryi on Helianthemum almeriense. In addition, they also found that bacterial isolates that produced auxins, significantly increased the root-shoot ratio and mycorrhizal colonization (Navarro-Ródenas et al 2016).…”
Section: Effect Of Plant-bacteria-fungi Interactions On Members Of Thmentioning
confidence: 99%
“…Another example is that of Navarro-Ródenas et al (2016) who isolated a Pseudomonas mandelii strain that increased mycorrhizal colonization of Terfezia claveryi on Helianthemum almeriense. In addition, they also found that bacterial isolates that produced auxins, significantly increased the root-shoot ratio and mycorrhizal colonization (Navarro-Ródenas et al 2016). Also, endobiotic bacteria residing inside fungal hyphae can have positive effects on mycorrhizal growth.…”
Section: Effect Of Plant-bacteria-fungi Interactions On Members Of Thmentioning
confidence: 99%